Integrability Analysis of a Two-Component Burgers-Type Hierarchy - Blackmore, D.; Özçağ, E.; Prykarpatsky, A. K.; Soltanov, K. N. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
The Lax integrability of a two-component polynomial Burgers-type dynamical system is analyzed by using a differential-algebraic approach. Its linear adjoint matrix Lax representation is constructed. A related recursive operator and an infinite hierarchy of nonlinear Lax integrable dynamical systems of the Burgers–Korteweg–de-Vries type are obtained by the gradient-holonomic technique. The corresponding Lax representations are presented.